Optimizing Employee Performance - Simbolon, Mai Rosmawati; Alifiah, Esti; Nurdiana, Editya (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study is aimed at analyzing the influence of emotional intelligence, competence, and career development on employee performance at UPTD PSDA WS Cimanuk-Cisanggarung. Design/methodology/approach: The study applied a quantitative research survey approach, involving 75 ASN and Non-ASN employees. Findings: The findings of this research paper indicate that emotional intelligence (t-value = 4.710 > t-table = 1.946, Sig. = 0.000 < 0.05), competence (t-value = 3.244 > t-table = 1.946, Sig. = 0.002 < 0.05), and career development (t-value = 4.724 > t-table = 1.946, Sig. = 0.000 < 0.05) all have a positive and significant influence on employee performance. Among these factors, career development exhibits the strongest influence. Research limitations/implications: The scope of this research is restricted to a sample of employees at UPTD PSDA WS Cimanuk-Cisanggarung, therefore the results may not be generalizable to other organizations. In addition, this study examines uses three independent variables without considering other factors that may also affect employee performance. Practical implications: This study provides recommendations for UPTD PSDA WS Cimanuk-Cisanggarung to provide more equitable career development opportunities, improve training programs, and strengthen emotional intelligence in the work environment to improve overall employee performance. Originality/value: This research offers a comprehensive understanding of the significance of emotional intelligence, competence, and career development in enhancing employee performance, particularly within Indonesia’s public sector organizations. Paper type: Research paper